Acute ethanol exposure-induced autophagy-mediated cardiac injury via activation of the ROS-JNK-Bcl-2 pathway - Zhu, Zhongxin; Huang, Yewei; Lv, Lingchun; Tao, Youli; Shao, Minglong; Zhao, Congcong; Xue, Mei; Sun, Jia; Niu, Chao; Wang, Yang; Kim, Sunam; Cong, Weitao; et al. (WILEY, 2018)
Binge drinking is associated with increased cardiac autophagy, and often triggers heart injury. Given the essential role of autophagy in various cardiac diseases, this study was designed to investigate the role of autophagy in ethanol-induced cardiac injury and the underlying mechanism. Our study showed that ethanol exposure enhanced the levels of LC3-II and LC3-II positive puncta and promoted cardiomyocyte apoptosis in vivo and in vitro. In addition, we found that ethanol induced autophagy and cardiac injury largely via the sequential triggering of reactive oxygen species (ROS) accumulation, activation of c-Jun NH2-terminal kinase (JNK), phosphorylation of Bcl-2, and dissociation of the Beclin 1/Bcl-2 complex. By contrast, inhibition of ethanol-induced autophagic flux with pharmacologic agents in the hearts of mice and cultured cells significantly alleviated ethanol-induced cardiomyocyte apoptosis and heart injury. Elimination of ROS with the antioxidant N-acetyl cysteine (NAC) or inhibition of JNK with the JNK inhibitor SP600125 reduced ethanol-induced autophagy and subsequent autophagy-mediated apoptosis. Moreover, metallothionein (MT), which can scavenge reactive oxygen and nitrogen species, also attenuated ethanol-induced autophagy and cell apoptosis in MT-TG mice. In conclusion, our findings suggest that acute ethanol exposure induced autophagy-mediated heart toxicity and injury mainly through the ROS-JNK-Bcl-2 signaling pathway.